2018
DOI: 10.1590/0102-311x00069817
|View full text |Cite
|
Sign up to set email alerts
|

Rastreadores para a busca ativa de eventos adversos a medicamentos em recém-nascidos

Abstract: The study aimed to verify the application and performance of triggers for adverse drug events in hospitalized newborns. This prospective cohort study was conducted in the neonatal care units of a university hospital from March to September 2015. A list of triggers was developed for the identification of adverse drug events in this population. The list included antidote, clinical, and laboratory triggers. A total of 125 newborns who had received drugs during the hospitalization were included. Neonatal patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…Rozenfeld et al . observed that hyperkalemia is a high-performance trigger to detect ADE in neonates 51. Serum potassium could also be used as a predictor of adverse clinical outcomes in patients with chronic ADE, and identify those likely to benefit from strategies that treat hyperkalemia, and prevent iRAAS discontinuation 52…”
Section: Discussionmentioning
confidence: 99%
“…Rozenfeld et al . observed that hyperkalemia is a high-performance trigger to detect ADE in neonates 51. Serum potassium could also be used as a predictor of adverse clinical outcomes in patients with chronic ADE, and identify those likely to benefit from strategies that treat hyperkalemia, and prevent iRAAS discontinuation 52…”
Section: Discussionmentioning
confidence: 99%
“…This information corroborates the data found in the selected articles, where studies using the IHI triggers identified 120 (Roque et al, 2018) and 44 (Giordani,et al, 2014) ADEs, and 79 (Roque et al, 2016) ADRs. While other trackers proposed by the authors identified 115 (Fabretti et al, 2018), 62 (Figueiredo et al, 2017) ADEs.…”
Section: Discussionmentioning
confidence: 86%
“…The triggers "abrupt medication stop" has shown similar performance in studies with adults and newborns. 10,21,22 Comparing the ability to detect ADE of each trigger, three groups were observed. The ones that showed the best performance were "excessive seda- tion/lethargy/fall/hypotension", "diphenhydramine use", and "phytomenadione use".…”
Section: Discussionmentioning
confidence: 99%
“…The calculated performance was categorized into three groups -high (100%), intermediate (between 30 and 70%), and low (< 30%). 9,10 This present study was approved by the Research Ethics Committees at Instituto Nacional de Saúde da Mulher, da Criança e do Adolescente Fernandes Figueira and at Hospital Universitário Antônio Pedro, registry numbers (CAAE) 68461417.7.0000.5243 and 68461417.7.3001.5269.…”
Section: Methodsmentioning
confidence: 99%